2022
DOI: 10.1002/fsn3.2775
|View full text |Cite
|
Sign up to set email alerts
|

The association among calorie, macronutrient, and micronutrient intake with colorectal cancer: A case–control study

Abstract: The risk of colorectal cancer (CRC) can be influenced by dietary components. This study aims to investigate the association between dietary intake and CRC in Iranian adults. This hospital‐based case–control study was performed on 160 patients with CRC and 320 healthy people. General and pathological data were collected through face‐to‐face interviews. A validated food frequency questionnaire (FFQ) was used to assess the intake of calories, macronutrients, and micronutrients. The case group had a significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
0
5
0
1
Order By: Relevance
“…There are few observational studies on manganese and CRC. The results of the case-control study found that manganese intake in CRC cases was lower than that in the control group, but no significant inverse association was found [30]. Animal experiments showed that tumor growth and metastasis were significantly enhanced in mice with manganese deficiency and tumor infiltration of CD8+ T cells was significantly reduced [31].…”
Section: Discussionmentioning
confidence: 93%
“…There are few observational studies on manganese and CRC. The results of the case-control study found that manganese intake in CRC cases was lower than that in the control group, but no significant inverse association was found [30]. Animal experiments showed that tumor growth and metastasis were significantly enhanced in mice with manganese deficiency and tumor infiltration of CD8+ T cells was significantly reduced [31].…”
Section: Discussionmentioning
confidence: 93%
“…Риск колоректального рака был отрицательно связан с приемом фолиевой кислоты (ОШ 0,98; 95% ДИ 0,97-0,98; р=0,001) и биотина (ОШ 0,83; 95% ДИ 0,77-0,90; р=0,001). Ассоциации оставались значимыми после поправки на возраст, пол, физическую активность, потребление алкоголя и курение [43].…”
Section: витамин в 7 (витамин н биотин)unclassified
“…However, conflicting findings have been reported in other studies. 7 Poor nutrition is well recognized as a significant contributing factor to mortality resulting from CRC. 8 Therefore, dietary modification may reduce cancer severity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to investigate the association between dietary patterns and the risk of developing CRC. 6 , 7 , 9 Several epidemiological studies have demonstrated the preventative properties of n‐3 long‐chain polyunsaturated fatty acids (n‐3 LCPUFAs) such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in relation to CRC. However, the impact of n‐3 LCPUFAs on CRC has been inconclusive.…”
Section: Introductionmentioning
confidence: 99%